+0

# Can you solve it?

0
314
1
y''+y'-6y=e^(-3x)?
Guest Feb 18, 2012
Sort:

#1
+3066
0
isaac3211:

y''+y'-6y=e^(-3x)?

first the complementary solution for: y''+y'-6y=0
y(x)=e^(λ*x)

e^(λ*x) d^2/dx^2 + e^(λ*x) d/dx - 6*e^(λ*x) = 0

substitute:
e^(λ*x) d^2/dx^2 with λ^2*e^(λ*x)
e^(λ*x) d/dx with λ*e^(λ*x)

λ^2*e^(λ*x)+λ*e^(λ*x)-6*e^(λ*x) = 0

(λ^2+λ-6)*e^(λ*x) = 0
solve:
λ^2+λ-6=0
λ=-3 and λ=2

so:
y1(x) = c1*e^(-3*x)
y2(x) = c2*e^(2*x)
(c1,c2 = constant)
=> the complementary solution y(x):
y(x) = y1(x)+y2(x) = c1*e^(-3*x) + c2*e^(2*x)

[input]diff(diff(y(x),x),x)+diff(y(x),x)-6*y(x)=0[/input]

ok, looks good. now to the particular solution: y''+y'-6y=e^(-3x)
yp(x) = x*a1*e^(-3x)

yp(x) d/dx = a1*e^(-3x)*-3*a1*e^(-3x)*x
[input]diff( x*a1*e^(-3x), x)[/input]

yp(x) d^2/dx^2 = a1*( -6*e^(-3x)+9*e^(-3x)*x )
[input]diff(diff( x*a1*e^(-3x), x),x)[/input]

now insert both diff'd yp(x) and yp(x) into y''+y'-6y=e^(-3x)
a1*( -6*e^(-3x)+9*e^(-3x)*x ) + a1*e^(-3x)*-3*a1*e^(-3x)*x - 6*x*a1*e^(-3x) = e^(-3x)
-5*a1*e^(-3x) = e^(-3x)
a1 = -1/5
yp(x) = -(1/5)*e^(-3x)*x

y(x) = c1*e^(-3*x) + c2*e^(2*x) + y(p)
y(x) = c1*e^(-3x) + c2*e^(2x) - (1/5)*e^(-3x)*x
admin  Feb 18, 2012

### 21 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details